2019
DOI: 10.1186/s12876-019-0935-y
|View full text |Cite
|
Sign up to set email alerts
|

The incidence, etiologies, outcomes, and predictors of mortality of acute liver failure in Thailand: a population-base study

Abstract: BackgroundAcute liver failure (ALF) is uncommon but progresses rapidly with high mortality. We investigated the incidence, etiologies, outcomes, and predictive factors for 30-day mortality in patients with ALF.MethodsWe conducted a population-based study of ALF patients hospitalized between 2009 and 2013 from the Thai Nationwide Hospital Admission database, which comprises 76% of all admissions from 858 hospitals across 77 provinces in Thailand. ALF was diagnosed using ICD-10 codes K72.0 and K71.11. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 28 publications
2
31
1
Order By: Relevance
“…It is not surprising to find renal injury as an independent predictor of 28‐day mortality of HEV‐LF, complying with prior studies . Furthermore, Urrunaga et.al not only found that renal dysfunction complicating ALF predicted a significantly worse outcome, but also emphasized the association between mortality and the degree of renal dysfunction .…”
Section: Discussionsupporting
confidence: 63%
“…It is not surprising to find renal injury as an independent predictor of 28‐day mortality of HEV‐LF, complying with prior studies . Furthermore, Urrunaga et.al not only found that renal dysfunction complicating ALF predicted a significantly worse outcome, but also emphasized the association between mortality and the degree of renal dysfunction .…”
Section: Discussionsupporting
confidence: 63%
“… 17 Our rate of liver transplant is similar to other studies from resource limited countries, owing to delayed referrals, rapidly worsening disease process and limitation of the procedure as well. 18 In contrast 10% of Paediatric liver transplants done in America are due to FHF. 19 Mortality was seen in 6 (21.4%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Then, after con rming the appropriate dose of modeling, we transplanted BMSCs to rats with liver failure, rats were divided into 3 groups: saline, TAA + saline, and TAA + saline + BMSCs (1×10 6 , intravenous injection). To collect samples, all rats were sacri ced by CO 2 asphyxiation.…”
Section: An Animal Model Of Acute Liver Failure and Cell Transplantationmentioning
confidence: 99%
“…Acute liver failure is characterized by sudden development of liver dysfunction and rapid hepatocellular necrosis, may progress to exhibit hepatic coma even death due to various of etiologies, including drug toxicity, hepatic ischemia, immune-mediated attack, and viral hepatitis such as hepatitis B and hepatitis C [1,2]. Endotoxemia represents the severe stage of acute liver failure and is associated with poor quality of life, mortality, and economic burden [3].…”
Section: Introductionmentioning
confidence: 99%